Implementasi Dan Efektivitas Pembelajaran Khat Naskhi Pada Mahasiswa Program Studi Pendidikan Bahasa Arab Universitas Negeri Makassar - Rabiatul Adawiyah Madawat M (CV. SINAR HOWUHOWU, 2026)
This study examines the implementation of Khat Naskhi learning among students of the Arabic Language Education Study Program (PBA) at Universitas Negeri Makassar (UNM). Khat Naskhi is one of the fundamental calligraphy scripts in Arabic writing, serving as an essential competency for Arabic language education students. This research uses a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation. The subjects were 30 students of PBA UNM in the academic year 2023/2024. The results indicate that the implementation of Khat Naskhi learning at PBA UNM employs a combination of direct demonstration, drill practice, and guided feedback methods. Learning outcomes show that 86.7% of students achieved the good and very good categories. The main challenges faced include the availability of calligraphy tools, limited practice time, and varied student backgrounds in Arabic script writing. These findings suggest that structured and systematic Khat Naskhi instruction significantly improves students' Arabic calligraphy competence.